Evaluation of pressure ulcer risk in hospitalized patients after metabolic surgery - Karaca, Fatih Can; Ulusan, Kıvılcım (Journal of Surgery and Medicine, 2020)
Aim: Patients who underwent surgery are in the risk group for development of pressure ulcers (PU) due to several factors including surgery time, immobilization and preexisting comorbidities. We aimed to evaluate the PU risk using The Braden Scale in patients during their hospitalization after sleeve gastrectomy with transit bipartition (SG+TB) surgery. Methods: This is a retrospective cohort study evaluating the PU risk using The Braden Scale, which consists of six subscales including sensory perception, moisture, activity, mobility, nutrition, and friction/shear. The patients were sub-grouped in terms of PU risk based on total Braden score. Results: The study group consisted of 33 patients who underwent SG+TB. The mean Braden score was 19.2(2.77) (range 12-23) during the hospitalization period. The Braden scores of the patients were lower on the 2nd (P<0.001), 3rd (P<0.001), 4th (P=0.005), and 5th (P=0.004) postoperative days compared to postoperative day 1, and on the 3rd, 4th, 5th, and 6th postoperative days compared to postoperative day 2 (P<0.001 for each). According to our data, the PU risk was significantly different between the 1st postoperative day and the 2nd, 3rd, 4th, and 5th postoperative days (P<0.001 for each). Conclusion: Metabolic surgery patients have an elevated risk for PU during the hospitalization period. Protein supplementation is among the factors that might improve the nutritional status of patients and decrease PU risk during hospitalization.